Analisis Kepuasan Pengguna Pada Website Pemda Kabupaten Dompu - Rahman, Fazlul; Setyanto, Arief; Henderi, Henderi (Forum Kerjasama Pendidikan Tinggi, 2022)
Dompu local government provides a website that provides information. Each interaction with the user gives rise to a variety of perceptions. One of them is the negative perception of the dompu community as a user of the website as well as the dompu local government as its supply organization. To reduce the problem of negative perceptions related to user experience in the process of using it, an evaluation of user experience is also done as well as an improved interface design. This research was conducted to determine the problems experienced by users by gathering various perceptions of the local government website. The test was carried out using a tool in the form of a User Experience Questionnaire (UEQ). The reason for using the UEQ method is because it is a quick and easy questionnaire to measure the user experience of a website. The results of evaluating user experience using UEQ, The results of evaluating user experience using UEQ show that aspects of perspicuity, efficiency, stimulation, novelty attractiveness and dependability: bad